2017
DOI: 10.23955/rkl.v12i1.5410
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Sorghum Starch-Cellulose Bioplastic with Sorghum Stalks Filler

Abstract: This study evaluated the modification of bioplastics production by various ratios of sorghum starch and cellulose from red seaweed eucheuma spinossum, and the use of glycerol as plasticizer and sorghum stalks as filler. Solid-liquid matrix transition should be far over the operating temperature of gelatinization and extracted at 95 o C in order to avoid the loss of conductivity. The analyzed variables were starch and cellulose seaweed eucheuma spinossum and the addition of variation of filler. Sorghum stalk ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…8 ) with powdered potato peels and wood dust as filler respectively presented similar results where samples with no filler added (except control) demonstrated the lowest absorption of water capacity whilst addition of filler demonstrated a steady increase in the water absorbance capacity. In a study by Darni et al, ( Darni et al, 2017 ), similar results were also noticed in which absorption of water was seen to increase when sorghum stalks filler was added into a sorghum starch based bioplastic. This can be attributed to sorghum stalks comprising of cellulose, and cellulose being hydrophilic.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…8 ) with powdered potato peels and wood dust as filler respectively presented similar results where samples with no filler added (except control) demonstrated the lowest absorption of water capacity whilst addition of filler demonstrated a steady increase in the water absorbance capacity. In a study by Darni et al, ( Darni et al, 2017 ), similar results were also noticed in which absorption of water was seen to increase when sorghum stalks filler was added into a sorghum starch based bioplastic. This can be attributed to sorghum stalks comprising of cellulose, and cellulose being hydrophilic.…”
Section: Discussionsupporting
confidence: 69%
“…Addition of filler was not found to add any new functional groups to the samples. In a similar former study on starch-based bioplastics, adding filler was also not found to add any new functional groups ( Darni et al, 2017 ).
Fig.
…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Bioplastic production using raw materials for empty bunches has been successfully carried out using modified cellulose, composites with plasticizers and compatilibizer [2]. The results of studies conducted by bioplastics were produced using starch and cellulose of seaweed eucheuma spinosum and the addition of sorghum stem fillers, which are thought to affect the mechanical and physical properties of bioplastics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups are making efforts to replace petroleum-based polymers by natural, biodegradable, and abundant products synthesized from renewable biomass [10,11]. Various biomacromolecules are present in nature, which could be utilized as renewable biomass for the production of nanohybrid materials such as starch, cellulose, lignin, polylactic acid (PLA), and other polyesters for the development of "greener" materials [12,13]. Their blends with natural inorganic materials, for example, nanocellulosic-clay and carboxymethylcellulose, provide enhanced biodegradability and biocompatibility among matrix molecules.…”
Section: Introductionmentioning
confidence: 99%